Mother-child relations in the context of prematurity and the importance of neonatal nursing: integrative review (Research, Society and Development, 2021)
Objective: to identify in the scientific literature feelings and perceptions evidenced by mothers of premature children admitted to the Neonatal Intensive Care Unit about interactions with the nursing staff. Method: integrative review conducted in November 2020. Studies published in full between 2015 - 2020 were captured, indexed in the MEDLINE, LILACS and BDENF databases, in Portuguese and English, submitted to qualitative synthesis. Results: 14 articles published in national and international magazines were selected. The analysis of the results, in a descriptive way, constituted three thematic categories: Ambiguous feelings and difficulties to realize motherhood; Kangaroo method as a significant strategy for affective bonding between mother and child and Welcoming the nursing team to families. Conclusion: Nursing care based on understanding the other, social interaction, welcoming and sharing the anxieties of mothers who have their newborns admitted to the Neonatal Intensive Care Unit shows the relevance of actions that promote the emotional bond between mothers and children.